A qualitative study to explore primary health care practitioners' perceptions and understanding regarding the COVID-19 pandemic in KwaZulu-Natal, South Africa - Celenkosini T. Nxumalo; Gugu G. Mchunu (AOSIS, 2021)
Background: The coronavirus disease 2019 (COVID-19) is a novel virus that has rapidly spread across countries globally, and has been declared a pandemic by the World Health Organization (WHO). In South Africa, more that 1 million cases have been confirmed since case zero was detected in March 2020. South Africa is currently leading in the sub-Saharan African region in terms of COVID-19-related mortality and morbidity rates. Aim: The aim of this study was to explore primary health care practitioners' perceptions and understanding regarding the COVID-19 pandemic in KwaZulu-Natal, South Africa. Setting: The study was conducted at two selected primary health care facilities (a community health centre and satellite clinic) within a low-income rural context in KwaZulu-Natal, South Africa. Methods: A qualitative study was conducted to explore and describe perceptions and understanding of primary health care practitioners regarding the COVID-19 pandemic in KwaZulu-Natal (KZN), South Africa. Data were collected from a purposive sample of 15 participants at two different clinics situated in rural KZN, South Africa. Participants comprised of nurses, physiotherapists, pharmacists, community care givers, social workers and clinical associates. The participants were both men and women who were all above the age of 20. Data were collected through individual, in-depth face-to-face interviews using a semi-structured interview guide. An audiotape was used to collect data, which were transcribed verbatim. Data were analysed manually by thematic analysis following Tech's steps of data analysis. Results: Participants reported pre-pandemic and pandemic perceptions of fear, denial, expectancy and a perceived poor preparation for the COVID-19 outbreak. The findings also revealed participants' misperceptions regarding the nature of the COVID-19 pandemic and unrealistic expectations of occupational compensations for working during the outbreak. Conclusion: The findings of this study suggest that primary health care practitioners generally have negative perceptions and understanding regarding the pandemic because of misinformation obtained from social media. Interventions to support health care practitioners are necessary to mitigate the potentially negative implications of health practitioners' misconceptions on service delivery and their mental health.